Effects of thermal treatment of ZnO-ZnCr2O4 catalyst on the particle size and product selectivity in dehydrocyclization of crude glycerol and ethylenediamine - Sarkari, Reema; Krishna, Vankudoth; Sudhakar, Medak; Rao, Tumula Venkateshwar; Padmasri, Aytam Hari; Srinivas, Darbha; Venugopal, Akula (Kinetics and Catalysis, 2016)
The ZnO-ZnCr2O4 (Zn-Cr-O) sample obtained by decomposition of Zn-Cr hydrotalcite precursor was subjected to the thermal treatment at different temperatures and the physico-chemical properties of the Zn-Cr-O system were compared with its catalytic behavior in dehydrocyclization of crude glycerol and ethylenediamine (EDA). Upon high temperature treatment of Zn-Cr-O the Cr6+ ions underwent autoreduction to form stable Cr3+ species and the particle size of both ZnO and ZnCr2O4 increased dramatically. Thermal effect did not influence the intermolecular cyclisation of EDA to form pyrazine. By contrast, an inversely proportional dependence was found between the rate of formation of 2-methylpyrazine and the particle size of Zn-Cr-O whereas the rate of 2-pyrazinylmethanol was directly proportional to the particle size.